VALIDITY AND RELIABILITY STUDY OF THE TURKISH ADAPTATION OF THE DIGITAL ADDICTION SCALE FOR TEENAGERS (DAST) - Çelik, Osman Tayyar; Tunç, Yunus; Candemir, Burcu; İçen, Betül Kapkın; Açar, Davut (My University, 2023)
The aim of this study is to adapt the \"Digital Addiction Scale for Teenagers\" developed by Seema, Heidmets, Konstabel and Varik-Maasik (2022) into Turkish. The study was carried out with 599 students studying in secondary and high schools. Within the scope of translation and language validity, firstly, the scale was translated from its original language, English, to Turkish. Afterwards, the Turkish statements were finalized with the consensus of the field and language experts. As a result of the CFA analysis, it was found that the scale had model fit (?²/Sd= 128.614/28=4.59; p<.05, CFI=.96; TLI=.95; GFI=.95; SRMR=.036; RMSEA=.079). It was concluded that factor load values varied between .56 and .79, and item-total test correlations varied between .62 and .79. As a result of the correlation analysis conducted for similar scale validity, it was determined that there was a high level of positive relationship between the \"Digital Addiction Scale for Teenagers\" and the \"Digital Game Addiction Scale\" at the level of .62 and with the \"Internet Addiction Scale\" at the level of .79. It was determined that the scale was able to distinguish between the upper and lower 27% groups (p<.05) and Cronbach's alpha reliability coefficient was calculated as .90. According to the validity and reliability analyses, it can be said that the Turkish form of the scale is valid and reliable.
Keywords: Validity; Reliability; Adolescents; Addiction; Digital addiction